AT 2019avd: A novel addition to the diverse population of nuclear transients - Malyali, A.; Rau, A.; Merloni, A.; Nandra, K.; Buchner, J.; Liu, Z.; Gezari, S.; Sollerman, J.; Shappee, B.; Trakhtenbrot, B.; Arcavi, I.; Ricci, C.; et al. (EDP SCIENCES S A, 2021)
We report on SRG/eROSITA, ZTF, ASAS-SN, Las Cumbres, NEOWISE-R, and Swift XRT/UVOT observations of the unique ongoing event AT 2019avd, located in the nucleus of a previously inactive galaxy at z = 0.029. eROSITA first observed AT 2019avd on 2020-04-28 during its first all sky survey, when it was detected as an ultra-soft X-ray source (kT 85 eV) that was a 90 times brighter in the 0.2-2 keV band than a previous 3σ upper flux detection limit (with no archival X-ray detection at this position). The ZTF optical light curve in the 450 days preceding the eROSITA detection is double peaked, and the eROSITA detection coincides with the rise of the second peak. Follow-up optical spectroscopy shows the emergence of a Bowen fluorescence feature and high-ionisation coronal lines ([Fea» X] 6375 Å, [Fea» XIV] 5303 Å), along with persistent broad Balmer emission lines (FWHM 1400 km s-1). Whilst the X-ray properties make AT 2019avd a promising tidal disruption event (TDE) candidate, the optical properties are atypical for optically selected TDEs. We discuss potential alternative origins that could explain the observed properties of AT 2019avd, such as a stellar binary TDE candidate, or a TDE involving a super massive black hole binary.